EKSPLORASI AKTIVITAS KEBUDAYAAN DESA WISATA MENARI TANON SEMARANG DALAM PEMBELAJARAN MATEMATIKA SD - Santi, Dina Pratiwi Dwi; Nurhidayah, Shanti; Anindiyah, Salsabila; Kurniawan, Verina Deawanny; Ulhaq, Najma Dhiya; Maharani, Dewi; Fitriawati, Titi; Cahyanti, Icih; Hafidhoh, Hikmalia Puspita; Sari, Rike Komala; Jannah, Raudhotul (Department of Mathematics Education, Universitas Kuningan, 2024)
Menari Tanon Village, Semarang, has a uniqueness and cultural diversity that is closely related to one of the mathematical concepts, namely geometry. So that it can be used as material for mathematics lessons in schools. This study aims to describe cultural activities in Menari Tanon Tourism Village, Semarang such as farming, livestock raising, dancing, and artifacts related to mathematics to be used as learning materials in elementary mathematics learning activities. The research method used is the method of observation and interviews with the Menari Village (Village Head, Founder of Dancing Tourism Village and Surrounding Communities). The results of the study show that Menari Tanon Village Semarang has cultural diversity related to learning mathematics in elementary schools such as recognizing flat shapes in farming activities, calculating geometric shapes in livestock activities, recognizing angles and lines in dancing activities, recognizing flat shapes on artifact studies. This research is expected to provide benefits for the development of elementary mathematics learning by raising the culture found in the Menari Tourism Village as a cultural tourism village.